Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan di Kopdit Mekar Sai: Studi Pada Koperasi Kopdit Mekar Sai Kota Bandar Lampung (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
The “main objective of this study is to investigate how employees of Kopdit Mekar Sai Bandar Lampung are motivated and how their work environment influences their performance. This study employs a quantitative research approach, with data collected through a survey using questionnaires distributed to sixty employees. In this research, employee performance is the dependent variable, while work motivation and work environment serve as the independent variables. Data analysis was conducted using IBM SPSS Statistics, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). Although the work environment shows a positive effect, it is partially not significant on employee performance, the findings indicate that work motivation has a positive and significant impact. Both the work environment and employee motivation play important roles in determining how well an organization performs its tasks. With an R² value of 0.606, it can be concluded that work motivation and work environment explain 60.6% of the variation in employee performance, while the remaining variation is influenced by variables outside the scope of this study. Based on these findings, employee motivation is the most important factor in improving performance at Kopdit Mekar Sai. Therefore, top management should prioritize initiatives that can motivate employees to give their best performance at work.